Pioneer factors in viral infection - Neugebauer, Eva; Bastidas-Quintero, Aura M.; Weidl, Daniel; Full, Florian (Frontiers in Immunology, 2023)
Pioneer factors are transcription factors sharing the fascinating ability to bind to compact chromatin and thereby alter its transcriptional fate. Most pioneer factors are known for their importance during embryonic development, for instance, in inducing zygotic genome activation or cell fate decision. Some pioneer factors are actively induced or downregulated by viral infection. With this, viruses are capable to modulate different signaling pathways resulting for example in MHC-receptor up/downregulation which contributes to viral immune evasion. In this article, we review the current state of research on how different viruses (Herpesviruses, Papillomaviruses and Hepatitis B virus) use pioneer factors for their viral replication and persistence in the host, as well as for the development of viral cancer.